Kajian tingkat efektivitas pembangunan Jalan Lingkar Sorong-Pelabuhan Arar - Mayaut, Yakobus; Massara, Asma; Bulgis, Bulgis (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
The enhancement of physical facilities and infrastructure is a governmental strategy aimed at improving public welfare, exemplified by the construction of ring highways in several Indonesian towns. The primary objective of constructing the ring road is to alleviate urban traffic congestion and enhance the movement of regional, inter-city, and local traffic, hence facilitating the efficient distribution of commodities at both regional and local levels. The Sorong Ring Road leads to Arar Port in Sorong Regency, situated on the westernmost edge of Papua Island, serving as the entry point to Papua. The terrain of Sorong Regency comprises mountains, slopes, hills, and lowland areas. To promote economic equality, the government plans to construct several large ports, with Sorong Regency designated as one of the sites for a larger port. This development will enhance the volume of maritime traffic in and out of the port. The research employs quantitative methodologies utilizing primary and sequential data collection procedures, alongside multiple linear regression analysis. The study’s results suggest that road network growth is a significant factor influencing congestion, accounting for 39.4% or a coefficient of 0.394, with a significance level of 0.000. This indicates that it is below 0.05, and it is asserted that the advantages of constructing the ring road network significantly impact the congestion issue in Sorong City. The determination coefficient is 0.672, indicating that 67.2% of the variables contributing to the congestion issue can be elucidated by the variable pertaining to Ring Road Network Development. The remaining 33% of variables were accounted for by unobserved factors in this study. The R value is 0.820, indicating a correlation of 0.820 between congestion (x1), side obstructions (x4), pollution (x5), and the ring road network concerning the congestion issue. This indicates a robust and favorable correlation in alleviating congestion, lateral obstructions, and air pollution.